'De-Securitising the Arctic' in Climate Change: An Indian Perspective. (December 2021) - Sharma, Bipandeep
The rapidly transforming Arctic has led to rethink the concept of security in the region. The increasing global warming and opening up of the Arctic have brought multiple geopolitical issues before the Arctic and non-Arctic states. 1 In pursuit of their perceived geopolitical, geo-economics and strategic interests, a race to 'securitise the Arctic' has started amongst the major Arctic states. This process of securitisation appears to be dictated and driven not only by traditional military-strategic considerations but also by non-traditional security threat dilemmas related to energy, environment, sustainability, human security, connectivity, etc. As the old and the new Arctic challenges are being taken out of the realm of 'normal politics' and placed in the contested domain of 'security politics', the Asian states, that are directly or indirectly impacted by the changing Arctic realise that securitisation of the Arctic is leaving little space for addressing common issues of global concern. This study argues that all these emerging issues (otherwise perceived as 'security threats') in the Arctic, instead of being addressed in the securitisation framework, could and should be approached and addressed as compelling reasons for mutual cooperation and thus in need of de-securitisation.